Pattern of ENT foreign bodies at Lumbini Zonal Hospital, a regional level ENT referral centre in Western Nepal - Pantha, Sandesh; Sharma, B (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Aim: Foreign bodies in ENT account for a significant number of visits to an ENT clinic. Our study was aimed to determine the load of foreign bodies in an ENT referral centre in western Nepal. Methods: It is a retrospective analysis of all the patients who presented with foreign bodies in the ENT department of the Lumbini Zonal Hospital over a period of 9 months from April-December 2009. Charts and outpatient register of the ENT department were retrospectively analyzed using SPSS 14.0. Results: Foreign bodies were predominant in the paediatric age group. Aural foreign bodies were the most common followed by nasal foreign bodies. Nonliving foreign bodies were more common than living foreign bodies. Conclusion: ENT foreign bodies can be removed safely in the outpatient clinic without much complication except for the foreign bodies in the oesophagus which require removal under general anaesthesia.